Social Cohesion in Ola Rotimi’s Kurunmi: A Resonance of History, Culture and Law - Yemi Atanda (Yoruba Studies Review)
The crisis of the Yoruba Nineteenth Century was a display of internal dissensions, internecine wars, and inter-personal ego. However, the Alaafn remained the ruler of the Oyo Empire, but depended on Ibadan and Ijaye for defense. In 1858, Alaafn Atiba summoned all the leading chiefs in his territory to introduce his Crown Prince, Adelu, as his successor. Tis move was against the constitution of Oyo, which stipulated that the Crown Prince (aremo) commits suicide on the Alafn’s death. Ibadan agreed to the change, while Ijaye opposed the imposition. This is the kernel of historical narrative used by Ola Rotimi, in constructing his play, Kurunmi, to refect rivalry between the Ibadan warriors and those of Ijaye. Tis essay examines the confict to refect and suggest the need for just, peace, and unity for social cohesion among Yoruba people, and by and large, Nigerians.